The emergence and spreading of an improved traditional soil and water conservation practice in Burkina Faso - Kaboré, Daniel; Reij, Chris (International Food Policy Research Institute, 2004)
This paper describes the emergence of improved traditional planting pits (zaï) in Burkina Faso in the early 1980s as well as their advantages, disadvantages and impact. The zaï emerged in a context of recurrent droughts and frequent harvest failures, which triggered farmers to start improving this local practice. Despair triggered experimentation and innovation by farmers. These processes were supported and complemented by external intervention. Between 1985 and 2000 substantial public investment has taken place in soil and water conservation (SWC). The socio-economic and environmental situation on the northern part of the Central Plateau is still precarious for many farming families, but the predicted environmental collapse has not occurred and in many villages indications can be found of both environmental recovery and poverty reduction. -- Authors' Abstract